2021
DOI: 10.25259/sni_522_2020
|View full text |Cite
|
Sign up to set email alerts
|

Fiberoptic bronchoscopy versus video laryngoscopy guided intubation in patients with craniovertebral junction instability: A cinefluroscopic comparison

Abstract: Background: Manipulation during endotracheal intubation in patients with craniovertebral junction (CVJ) anomalies may cause neurological deterioration due to underlying instability. Fiberoptic-bronchoscopy (FOB) is better than video laryngoscope (VL) for minimizing cervical spine movement during intubation. However, evidence suggesting superiority of FOB in patients with CVJ instability is lacking. We prospectively compared dynamic movements of the upper cervical spine during intubation using FOB with VL in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This has been seen to offer a similar advantage to fiberoptic intubation under general anesthesia in terms of spinal kinematics in craniovertebral junction anomalies/instability. 5 …”
Section: Discussionmentioning
confidence: 99%
“…This has been seen to offer a similar advantage to fiberoptic intubation under general anesthesia in terms of spinal kinematics in craniovertebral junction anomalies/instability. 5 …”
Section: Discussionmentioning
confidence: 99%
“…However, studies are yet to prove if these movements are favorable or unfavorable. A study conducted by Agrawal et al 40 has compared videolaryngoscopes with fiberoptic bronchoscopy in patients with craniovertebral junction instability. They have observed that the patients intubated with videolaryngoscopy have shown a greater increase in the upper spinal canal diameter when compared with FOB.…”
Section: Aerodynamics Of C-spine During Intubationmentioning
confidence: 99%
“…Other airway devices have also been successfully used in patients with restricted or confined C-spine injuries, including supraglottic airway devices, gum elastic bougies, and rigid endoscopes [ 14 , 15 , 16 ]. Flexible fiberoptic laryngoscopes and/or bronchoscopes remained as the gold standard for suspected or confirmed C-spine injuries for many years [ 17 , 18 , 19 , 20 , 21 ]. The pros and cons of the available airway management tools for patients with a potential cervical spine injury have been reviewed [ 1 ].…”
Section: Introductionmentioning
confidence: 99%